2017
DOI: 10.1371/journal.pone.0185481
|View full text |Cite
|
Sign up to set email alerts
|

Plant water potential improves prediction of empirical stomatal models

Abstract: Climate change is expected to lead to increases in drought frequency and severity, with deleterious effects on many ecosystems. Stomatal responses to changing environmental conditions form the backbone of all ecosystem models, but are based on empirical relationships and are not well-tested during drought conditions. Here, we use a dataset of 34 woody plant species spanning global forest biomes to examine the effect of leaf water potential on stomatal conductance and test the predictive accuracy of three major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
98
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(105 citation statements)
references
References 70 publications
7
98
0
Order By: Relevance
“…Several recent studies have suggested that Ψ leaf should be incorporated into models of g s (e.g. Anderegg et al, ; Drake et al, ; Sperry et al, ; Venturas et al, ; Zhou et al, ). However, in our study the data do not support this argument, at least for the tropical evergreen canopy trees analyzed here (Figures and ; Figure S5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several recent studies have suggested that Ψ leaf should be incorporated into models of g s (e.g. Anderegg et al, ; Drake et al, ; Sperry et al, ; Venturas et al, ; Zhou et al, ). However, in our study the data do not support this argument, at least for the tropical evergreen canopy trees analyzed here (Figures and ; Figure S5).…”
Section: Discussionmentioning
confidence: 99%
“…This can arise either from the shorter timescale (e.g. diurnal) coordinated variation between leaf water potential and D (Anderegg et al, ), from the increasing soil moisture stress that can induce the associated change in plant water potential which down‐regulates g s and thus the slope parameters (e.g. Drake et al, ; Heroult et al, ; Zhou et al, ), or there is coordinated acclimation of the slope parameter with seasonal variation in soil moisture and plant water potential (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, it is still unlikely that state‐of‐the‐art climate models accurately represent the potential of droughts and heatwaves to self‐intensify via land feedbacks. However, there is significant progress in model representation of the transpiration response to stress conditions in land surface schemes; a more evolved coupling of transpiration to photosynthesis involving the explicit characterization of plant hydraulics is slowly becoming a reality . Since these processes affect the temporal and spatial response of land evaporation during droughts and heatwaves, their improved representation in land surface schemes is expected to have an impact on the projected duration and intensity of the events.…”
Section: Current Challengesmentioning
confidence: 99%
“…Mechanistic models provide insight, but are incomplete and can be difficult to parameterize (Buckley & Mott, ). Most canopy‐scale models (Tuzet et al ., ; Powell et al ., ; Anderegg et al ., ; Drake et al ., ) resort to empirical representations of stomatal conductance ( G ):G=f(A,C,WS,c1,c2ci)where A is the rate of photosynthesis, C is CO 2 concentration either in the leaf or air, WS is a measure of soil or plant water status, and c 1 , c 2 , etc., are empirically determined coefficients that are usually constant for a particular species or functional type. At each time step, submodels based on photosynthetic biochemistry, diffusion and hydraulics of plant and/or soil provide the array of physiologically possible choices for G , A , C and WS.…”
Section: Introductionmentioning
confidence: 99%